INVESTIGATING THE WAYS TO IMPROVE ESSAY WRITING BY IELTS STUDENTS - Muhammad Safdar Bhatti (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2021)
English is being learned and used all over the world. It has become a Lingua Franca and a language of more significant opportunities. It also exercises a great influence on the elite class of the country. Its knowledge is a successful passport for employment. Both oral and written skills are essential for learning a language. Learning a second language is never easy. Students must wrestle with new vocabulary, rules for grammar and sentence structure, idioms, pronunciation, and more. Some people seem to catch on much more quickly than others. Writing is a productive skill, and its primary concern is to give an insight into grammatical rules and composition writing. So the current paper evaluates the ways to improve students' efficiency while attempting argumentative essays in the IELTS Test conducted by the British Council of Pakistan. The researcher has studied the reasons behind these deficiencies and has paved the ways that may help English language teachers and students as they work with developing language skills for academic and social success. The sample of the study was taken from a local academy of Bahawalpur. The data was collected by using a pre-test, post-test, and questionnaire. The participants included ten teachers and 100 students of IELTS. The findings of the study proved the hypothesis correct. The conclusion with suggestions and recommendations was summed up at the end of the study.